Producing Knowledge with Care : Building Mutually Caring Researcher-research Participants Relationships - Sander, Alena (My University, 2021)
Today’s development studies are going through a decolonial turn. At the heart of the debates surrounding the turn are discussions about the relationship between the researcher – often from the Global Norths – and her research participants – often from the Global Souths, and how this relationship may be constructed in a more reciprocal and respectful way. This paper uses the example of the author’s dissertation research with Jordanian women’s organizations in 2017 and 2018. It looks into how the feminist mutual-care-approach developed by Joan Fisher and Berenice Tronto may inform a reciprocal and respectful way of doing research and producing knowledge with and in the Souths in practice, and looks into the challenges that may arise from it.
Keywords: Care; development studies; Ethik; Feminismus; research ethics; ddc:300